2010
DOI: 10.1590/s0034-72802010000600003
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do nível de conhecimento quanto ao uso de lentes de contato entre os estudantes de medicina da Faculdade de Medicina do ABC

Abstract: RESUMOObjetivo: Analisar o nível de conhecimento dos usuários de lentes de contato entre os estudantes de medicina da Faculdade de Medicina do ABC (SP) quanto aos cuidados, formas de uso, às complicações e à aquisição das lentes. Métodos: Foi aplicado um questionário a todos os alunos usuários de lentes de contato do 1º ao 6º ano de medicina da Faculdade de Medicina do ABC (SP), analisando-se por fim os resultados encontrados. Todos os questionários aplicados foram respondidos. Resultados: 61 estudantes respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
2
1
1
2
Order By: Relevance
“…In the present investigation, the demographic data is similar to those observed by other authors both in Brazil and in other countries, women were predominant, the age was between 20-49 years, and with complete high school (4,(6)(7)(8)(9)(10) .It is suggested that this finding is due to the fact of women, especially the younger, give more value the aesthetic appearance and contact lenses having optical, occupational, sports and cosmetic advantages (11) . Regarding the economic aspect, our study showed that most of patients (36.23%) had monthly income between 2 to 6 minimum wages.…”
Section: Table 4 Patients Who Don't Use Contact Lensessupporting
confidence: 88%
See 3 more Smart Citations
“…In the present investigation, the demographic data is similar to those observed by other authors both in Brazil and in other countries, women were predominant, the age was between 20-49 years, and with complete high school (4,(6)(7)(8)(9)(10) .It is suggested that this finding is due to the fact of women, especially the younger, give more value the aesthetic appearance and contact lenses having optical, occupational, sports and cosmetic advantages (11) . Regarding the economic aspect, our study showed that most of patients (36.23%) had monthly income between 2 to 6 minimum wages.…”
Section: Table 4 Patients Who Don't Use Contact Lensessupporting
confidence: 88%
“…Different from the literature, this research shows that 33.33% use it an average of 9 and 16 hours a day, while Lui et al calculated that 86.9% use CL for more than 8 hours a day, being DISCUSSION the average usage between 8 and 16 hours per day (75.4%) (8) . A large percentage of users still exceed 12 hours a day, longer than the recommended time, increasing the risk of complications.…”
Section: Table 4 Patients Who Don't Use Contact Lensescontrasting
confidence: 88%
See 2 more Smart Citations
“…Um fator que estimulou o aumento do uso de lentes foi o processo de fabricação das lentes de contato, que aumentou sua qualidade e diminuiu o custo de produção. Os materiais tem causado menos danos à fisiologia ocular e seus formatos são adequados a topografia corneana (OLIVEIRA et al, 2004 ;LUI et al, 2010). Para a fabricação de lentes oftálmicas faze-se necessária à utilização de uma água ultra pura, ou seja, isenta de partículas, íons e substâncias orgânicas ou microorganismos (LUI et al, 2010).…”
Section: Introductionunclassified